A FAHP-FTOPSIS approach for choosing mid-term occupational healthcare measures amid the COVID-19 pandemic. Issue 2 (June 2021) - Chen, Toly
Highlights: Existing occupational healthcare guidelines and practices amid the COVID-19 pandemic are reviewed. Mid-term occupational healthcare measures amid the COVID-19 pandemic are proposed. The FAHP-FTOPSIS approach is proposed to choose the most suitable mid-term occupational healthcare measure. Abstract: Background: The COVID-19 pandemic has severely affected factories all over the world. Occupational health care in factories has become a challenging task. In order to accomplish this task, it is necessary to change the production environment of a factory by adopting mid-term (to long-term) occupational healthcare measures is necessary. However, most of the guidelines and checklists provided by governments and international health organizations focus on short-tern responses to the pandemic. There are very few suggestions on what a factory should do in the medium to long term. This research aims to establish a systematic procedure for selecting suitable mid-term occupational healthcare measures for a factory amid the COVID-19 pandemic. Method: A fuzzy analytic hierarchy process (FAHP) and fuzzy technique for order preference by similarity to ideal solution (FTOPSIS) approach is proposed. In the proposed FAHP-FTOPSIS approach, FAHP is applied to derive the fuzzy priorities of factors that are critical to the suitability of a mid-term occupational healthcare measure based on the subjective judgments of a decision maker. Subsequently, the derived fuzzy priorities are input into FTOPSIS to evaluate the overall performance of a mid-term occupational healthcare measure. After considering five criteria, the best-performing mid-term occupational healthcare measure is the most suitable measure and will be selected by the factory. Results: The FAHP-FTOPSIS approach has been applied to compare the overall performances of four mid-term occupational healthcare measures for a factory based on the subjective judgment of a decision maker. According to the experimental results, the most suitable mid-term occupational healthcare measure for the factory was "isolating machines", followed by "further automation". Conclusions: A suitable mid-term occupation healthcare measure needs to effectively prevent the spread of COVID-19 and be accepted by workers, and should have low estimated total costs, low interference with existing operations, and seamless integration with other functional activities. The priorities of these critical factors depend on the subjective judgment of a decision maker. Therefore, different decision makers will come to different conclusions.